2020
DOI: 10.14569/ijacsa.2020.0110148
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Mobile Assisted Language Learning in Primary Education

Abstract: Literacy & Numeracy Drive (LND) is a mobile application that is used in public sector primary schools in Punjab province, Pakistan to teach students of Grade 03 on a tablet for learning languages and Mathematics. Persons designated the role of a Monitoring & Evaluation Assistant (MEA) visit every school allocated by authorities once in a month and select 07-10 students randomly to evaluate them on his own tablet by asking multiple questions related to English, Urdu and Mathematics. After the evaluation, MEA ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…, writing, reading, listening and speaking (Chang et al, 2013), listening comprehension (Çakmak & Erçetin, 2017), grammar (Chu, Wang & Wang, 2019) and reading comprehension (Ishaq et al, 2020b). The results presented by studies for the applications of pedagogy, reading, pronunciation, writing, listening, speaking, grammar outperformed the control group.…”
Section: Discussion and Future Directionsmentioning
confidence: 97%
See 4 more Smart Citations
“…, writing, reading, listening and speaking (Chang et al, 2013), listening comprehension (Çakmak & Erçetin, 2017), grammar (Chu, Wang & Wang, 2019) and reading comprehension (Ishaq et al, 2020b). The results presented by studies for the applications of pedagogy, reading, pronunciation, writing, listening, speaking, grammar outperformed the control group.…”
Section: Discussion and Future Directionsmentioning
confidence: 97%
“…The results presented by studies for the applications of pedagogy, reading, pronunciation, writing, listening, speaking, grammar outperformed the control group. It may be concluded that mobile applications for vocabulary learning have a positive impact on language learning in which pupils from the experimental group outperformed the control group except (Klimova & Polakova, 2020) (Ishaq et al, 2020b) where the students and teachers mentioned they are not satisfied with the design, content, assessment methods adopted in the applications besides pronunciation support and teachers' notifications were also missing. Gamified applications are proposed for vocabulary learning (Sandberg, Maris & Geus, 2011) (Sandberg, Maris & Hoogendoorn, 2014) (Wu, 2018) (Chen, Liu & Huang, 2019) (Fisser, Voogt & Bom, 2012), Spanish language learning (Holden & Sykes, 2011), Idioms (Amer, 2014), Vocabulary, Grammar, and Sentence Structure (Tsai et al, 2016), and Tenses, Words, Sentences (Önal, Çevik & Şenol, 2019).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations